Analysis of the learning curve for pre‐cut corneal specimens in preparation for lamellar transplantation: a prospective, single‐centre, consecutive case series prepared at the Lions New South Wales Eye Bank. (21st March 2017) - Martin, Aifric Isabel; Devasahayam, Rajnesh; Hodge, Christopher; Cooper, Simon; Sutton, Gerard L
Abstract: Importance: This study is the first paper to establish a learning curve by a single technician. Background: Preparation of pre‐cut corneal endothelial grafts commenced at Lions New South Wales Eye Bank in December 2014. The primary objective of this study was to review the safety and reliability of the preparation method during the first year of production. Design: This is a hospital‐based, prospective case series. Participants: There were 234 consecutive donor corneal lenticules. Methods: Donor lenticules were prepared by a single operator using a linear cutting microkeratome. Immediately prior to cutting, central corneal thickness values were recorded. Measurements of the corneal bed were taken immediately following lenticule preparation. Outcomes were separated by blade sizes, and intended thickness was compared to actual thickness for each setting. Early specimens were compared to later ones to assess for a learning curve within the technique. Main Outcome Measure: The main parameter measured is the mean difference from intended lamellar cut thickness. Results: The mean final cut thickness was 122.36 ± 20.35 μm, and the mean difference from intended cut was 30.17 ± 37.45 μm. No significant difference was found between results achieved with early specimens versus those achieved with later specimens ( P = 0.425). Conclusions and Relevance: Thin, reproducible endothelial grafts can routinely be produced by trained technicians at their respective eye banks without significant concerns for an extended learning curve. This service can reduce perioperative surgical complexity, required surgical paraphernalia and theatre times. The consistent preparation of single‐pass, ultrathin pre‐cut corneas may have additional advantages for surgeons seeking to introduce lamellar techniques.